2023
DOI: 10.1002/mrm.29675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of contributors to amide proton transferweighted imaging and nuclear Overhauser enhancementweighted imaging contrast in tumors at a high magnetic field

Abstract: Purpose:The purpose is to evaluate the relative contribution from confounding factors (T 1 weighting and magnetization transfer) to the CEST ratio (CESTR)-quantified amide proton transfer (APT) and nuclear Overhauser enhancement (NOE) (−3.5) in tumors as well as whether the CESTR can reflect the distribution of the solute concentration (f s ). Methods:We first provided a signal model that shows the separate dependence of CESTR on these confounding factors and the clean CEST/NOE effects quantified by an apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…More detailed statistical data can be found in the supporting information Tables S6 and S7. It was observed that while no significant difference was observed in APT between tumors and normal tissues for all denoising methods except the DCAE in APT imaging, there was a significant difference in NOE(-3.5), consistent with previous findings (15,(55)(56)(57).…”
Section: Comparison With State-of-the-art Methods Via Animal Experimentssupporting
confidence: 89%
See 1 more Smart Citation
“…More detailed statistical data can be found in the supporting information Tables S6 and S7. It was observed that while no significant difference was observed in APT between tumors and normal tissues for all denoising methods except the DCAE in APT imaging, there was a significant difference in NOE(-3.5), consistent with previous findings (15,(55)(56)(57).…”
Section: Comparison With State-of-the-art Methods Via Animal Experimentssupporting
confidence: 89%
“…The DCAE-CEST model was trained using simulated CEST signals, the parameters for which were derived from literature reviews (6,56,(58)(59)(60)(61)(62)(63)(64)(65) or based on our prior knowledge and experiences. Nonetheless, accurately quantifying the underlying CEST parameters remains a challenging task, primarily due to the difficulty to accurately isolate each CEST pool.…”
Section: Discussionmentioning
confidence: 99%
“…However, estimating APT k sw remains challenging due to the overlapping contributions 53,54 and the different exchange and relaxation rate selectivity of different quantification methods 55 . Consequently, diverse k sw values using different fitting models and quantification methods have been reported 54–59 . The current study may suggest higher k sw values for the APT effect isolated by the DSP‐CEST method.…”
Section: Discussionmentioning
confidence: 78%
“…55 Consequently, diverse k sw values using different fitting models and quantification methods have been reported. [54][55][56][57][58][59] The current study may suggest higher k sw values for the APT effect isolated by the DSP-CEST method. Similarly, no significant difference was found in the NOE (−3.5 ppm), which differs from the multiple-pool Lorentzian fitted NOE (−3.5 ppm) effect as shown in both Figure 8 and the previous report.…”
Section: F I G U R Ementioning
confidence: 83%
“…Our findings indicate that their influences to the variation of CESRT signal in tumors cannot be ignored, and the "shine through" effect from MT to the CEST ratio is more significant at higher saturation powers. 41 Consequently, it is crucial to use the AREX metric to mitigate the influences from the variation in T 1 weighting and MT effect when evaluating the relative contributions from amide, amine and guanidine proton transfer effects to the APTw contrast in specific pathologies.…”
Section: Discussionmentioning
confidence: 99%